Negosiasi Maskulinitas dan Harga Diri Suami: Analisis Sosio-Kultural pada Keluarga Migran - Hasani (Kartika: Jurnal Studi Keislaman, 2026)
The phenomenon of female labor migration from Jatisari Village, Jenggawah District, Jember has triggered profound socio-cultural shifts within household structures. This study examines how husbands from migrant families negotiate their masculinity and self-esteem within the cultural context of Javanese rural communities, which remain strongly shaped by patriarchal values. Using a phenomenological qualitative approach, this research analyzes the social role dynamics of husbands left behind, community pressures, and adaptive strategies employed in responding to these changes. Data were collected through in-depth interviews with 12 husbands whose wives work as female migrant workers abroad, participatory observation, and documentary study. Findings reveal that masculinity negotiation occurs through three principal socio-cultural mechanisms: (1) redefinition of domestic roles without sacrificing symbolic authority within community norms; (2) mobilization of social-kinship networks as sources of cultural legitimation; and (3) internalization of local and religious values as a psycho-cultural foundation. Husbands' self-esteem does not entirely collapse but undergoes an adaptive and contextual reconstruction aligned with local cultural dynamics. These findings contribute to the understanding of gender transformation in Javanese rural communities and its implications for migrant family empowerment policy